PENGARUH PERBEDAAN JENIS UMPAN DAN MATA PANCING TERHADAP HASIL TANGKAPAN PADA PANCING COPING (hand line) DI DAERAH BERUMPON PERAIRAN PACITAN, JAWA TIMUR - Siswoko, Paris; Wibowo, Pramono; Fitri, Aristi Dian Purnama (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Production fisheries in the waters of Pacitan increase, recorded in 2008 data about 1692.179 tons and in 2011 increased by 4544.863 tons. Effort to exploitation the fishery resources can do in various ways, catching is one of the efforts in the field of fisheries, whether it's catching in the sea, lakes or rivers. Catching effort requires a fishing gear, one of which is coping (hand line) where used fishing in the waters of Pacitan. Using different of bait and hook expected to give different catches. The purpose of this study was to analyze the effect of the type of imitation bait and natural bait, use a single hook and three hook, as well as to determine whether there is interaction of both factors. The method used is experimental fishing, and data collected in this study is the primary form of data directly from the field objects and documentation, as well as secondary data from production data in relevant institution. Data retrieval was conducted in March-April 2012. From the research data that have been obtained if the results that the use of a single hook and imitation bait most of their catch 138 fish. No interaction of the two treatments.